Cancer Therapy: Surface Nanopore Engineering of 2D MXenes for Targeted and Synergistic Multitherapies of Hepatocellular Carcinoma (Adv. Mater. 25/2018). Issue 25 (15th June 2018) - Li, Zhenli; Zhang, Han; Han, Jun; Chen, Yu; Lin, Han; Yang, Tian
Abstract : In article number1706981, Yu Chen, Tian Yang, and co‐workers report the development of a novel 2D MXene‐based composite nanoplatform for highly efficient and synergistic chemotherapy and photothermal hyperthermia against hepatocellular carcinoma (HCC). This work not only provides a novel strategy for efficiently combating HCC by developing MXene‐based composite nanoplatforms, but also paves a new way for extending the biomedical applications of MXenes by surface‐nanopore engineering.